In the name of honor : a novel - Patterson, Richard North (New York : Henry Holt, 2010)
Capt. Paul Terry, one of the army's most accomplished young lawyers, must defend Brian McCarran, a general's son who recently returned from a harrowing tour in Iraq. In the high-profile court-martial, Terry is joined by Brian's sister, Meg McCarran, who leaves her practice in San Francisco to help save her brother. Before the case is over, Terry will become deeply entwined with Meg and the McCarrans--and learn that families, like war, can break the sturdiest of souls.
Keywords: Iraq War, 2003-2011 -- Veterans -- Fiction; War -- Psychological aspects -- Fiction; Families of military personnel -- Fiction